2014
DOI: 10.1093/nar/gku300
|View full text |Cite
|
Sign up to set email alerts
|

Sumoylation of the Rad1 nuclease promotes DNA repair and regulates its DNA association

Abstract: The Saccharomyces cerevisiae Rad1-Rad10 complex is a conserved, structure-specific endonuclease important for repairing multiple types of DNA lesions. Upon recruitment to lesion sites, Rad1-Rad10 removes damaged sequences, enabling subsequent gap filling and ligation. Acting at mid-steps of repair, the association and dissociation of Rad1-Rad10 with DNA can influence repair efficiency. We show that genotoxin-enhanced Rad1 sumoylation occurs after the nuclease is recruited to lesion sites. A single lysine outsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 80 publications
5
28
0
Order By: Relevance
“…Whether SLX4 defines a novel class of SUMO E3 ligases structured around the BTB domain awaits the identification of additional BTB proteins with SUMO-E3 ligase activity. Interestingly, as we were finalizing our study, Slx4 was reported to be necessary in S. cerevisiae for SUMOylation of Rad1 XPF by Siz1 and Siz2 SUMO E3 ligases (Sarangi et al, 2014). Our results show that evolution has provided the human protein with the ability to directly SUMOylate XPF and that this relies on the acquisition of the BTB domain absent in the yeast protein.…”
Section: Slx4 a New Type Of Sumo E3 Ligase?supporting
confidence: 53%
“…Whether SLX4 defines a novel class of SUMO E3 ligases structured around the BTB domain awaits the identification of additional BTB proteins with SUMO-E3 ligase activity. Interestingly, as we were finalizing our study, Slx4 was reported to be necessary in S. cerevisiae for SUMOylation of Rad1 XPF by Siz1 and Siz2 SUMO E3 ligases (Sarangi et al, 2014). Our results show that evolution has provided the human protein with the ability to directly SUMOylate XPF and that this relies on the acquisition of the BTB domain absent in the yeast protein.…”
Section: Slx4 a New Type Of Sumo E3 Ligase?supporting
confidence: 53%
“…Similarly, a DNA binding mutation in the PCNA-like UL44 protein also impairs its sumoylation [31]. In some cases, DNA repair engagement, rather than simply DNA association, is required for sumoylation, as seen for the yeast Rad1 nuclease and human FANCI and FANCD2 proteins [32, 33]. Taken together, these new findings in different organisms suggest that DNA association and repair engagement are conserved requirements for the sumoylation of multiple DNA metabolism proteins.…”
Section: Low Level Of Substrate Sumoylation Can Be Linked To On-site mentioning
confidence: 99%
“…First, sumoylation levels of some of these proteins increase in situations when they are more active. For example, the sumoylation of several DNA repair proteins is induced when cells are treated with the DNA damaging agents that elicit repair activities from that protein, with higher genotoxin dosage having a stronger effect [6, 33, 36]. Along the same lines, sumoylation levels of some substrates peak in the cell cycle stage at which they are most active [15, 37, 38].…”
Section: Low Level Of Substrate Sumoylation Can Be Linked To On-site mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have identified roles for SUMO in modulating DNA repair (8998). The work presented here suggests SUMO-mediated regulation could extend to the evolutionarily conserved BER pathway.…”
Section: Discussionmentioning
confidence: 99%